The Effect of Childhood Trauma in Joseph Moldover’s Novel Every Moment After (2019) - Angellisa Pratami Salman; Leni Marlina (English Language and Literature, 2022)
This article is an analysis of the issue of the effect of childhood trauma in Joseph Moldover's novel entitled Every Moment After (2019). The issue at hand is the extent to which this novel depicts the consequences that arise and affect a person's personality after experiencing childhood trauma, as well as the contribution of literary elements such as characters, conflicts, and settings that rely on text-based interpretations to reveal these consequences. The goal of this analysis is to examine how well the novel depicts the effect of childhood trauma on a person's daily life and affects their mental health and mental illness. The analysis is based on Sigmund Freud's (1957, 1990) literary theory of repression and the unconscious mind. The result of the study, there are two impacts that develop after suffering childhood trauma that affect their mental health, such as anxiety and guilt. Anxiety that is owned by the character makes him afraid of dealing with other people, so it interferes with the character in interacting with other people. The guilt that the character also has makes him someone who always blames himself and even makes the character want to end his life. Therefore, this analysis shows how childhood trauma greatly affects a person's life and makes them have some mental illnesses.